Application of TL16C752 in Power Dispatching of Photovoltaic Inverter - ZHAO Xianggui; WU Hengliang; CHEN Yifeng; WANG Nan; ZHANG Rong (Kongzhi Yu Xinxi Jishu)
According to the status of huge amounts of communication data and high real-time performance for photovoltaic inverter, a communication program was presented based on DSP and TL16C752 type extended asynchronous serial communication device chip. The communication mode of TL16C752 and the protocol of Modbus communication for photovoltaic plant were studied, and the UART (universal asynchronous receiver transmitter) communication procedures were designed. It can realize power dispatching of 500 kW grid-connected inverter with this proposal. Experimental results show that the problem of communication between high speed DSP and low speed peripherals through asynchronous serial port can be solved effectively, and the real-time performance and reliability of the photovoltaic inverter communication system are enhanced.